Stress and Displacement Analysis of Dental Implant Threads Using Three-Dimensional Finite Element Analysis - Yodrux, Aswin; Yodpijit, Nantakrit; Jongprasithpornt, Manutchanok (Applied Science and Engineering Progress, 2019)
Dental implant is one of the most common ways to replace a missing tooth. The objective of this research project is to analyze the compressive stress, shear stress, and displacement of prosthetic tooth. This research is conducted using a three-dimensional finite element method to analyze biomechanical characteristics on dental implant systems at four different areas: abutment, implant, cortical bone, and cancellous bone. This research focuses on a variety of patents of dental implant threads from the United States Patent and Trademark Office. Findings reveal a new conceptual design of dental implant thread model. It is found that the maximum stress concentration is found at cortical bone but is still lower than the yield strength of materials. The new design of dental implant tread provides the minimum compressive stress, shear stress, and displacement for dental implant systems.